2021
DOI: 10.1515/jpm-2021-0173
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 in asymptomatic pregnant women in South Brazil: RT-PCR and serological detection

Abstract: Objectives This study aims to detect the SARS-CoV-2 infection prevalence in asymptomatic pregnant women. Methods A group of 195 asymptomatic pregnant women who attended the prenatal care outclinic and to the obstetric emergency department was tested concomitantly for SARS-CoV-2 by RT-PCR and serological tests. Results The virus was detected by RT-PCR in two (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“… 19 In Brazil, of 195 pregnant women, 1.02% of them were diagnosed with COVID‐19 by RT–PCR tests, and 8.7% were diagnosed with serological tests. 20 These studies are in contrast with our results because we found a higher prevalence, but the pregnant number analyzed in this study was lower in comparison with other study in Mexico City. 21 , 22 More studies are needed to determine the prevalence of COVID‐19 in pregnant women, because there are only few reports which show the pregnant women prevalence with SARS‐CoV‐2.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“… 19 In Brazil, of 195 pregnant women, 1.02% of them were diagnosed with COVID‐19 by RT–PCR tests, and 8.7% were diagnosed with serological tests. 20 These studies are in contrast with our results because we found a higher prevalence, but the pregnant number analyzed in this study was lower in comparison with other study in Mexico City. 21 , 22 More studies are needed to determine the prevalence of COVID‐19 in pregnant women, because there are only few reports which show the pregnant women prevalence with SARS‐CoV‐2.…”
Section: Discussioncontrasting
confidence: 99%
“…In northern California, a COVID‐19 prevalence of 2.5% was found in pregnant women 19 . In Brazil, of 195 pregnant women, 1.02% of them were diagnosed with COVID‐19 by RT–PCR tests, and 8.7% were diagnosed with serological tests 20 . These studies are in contrast with our results because we found a higher prevalence, but the pregnant number analyzed in this study was lower in comparison with other study in Mexico City 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…The serological evaluation was mainly carried out at the time of hospitalization, at the time of delivery, or randomly during pregnancy. However, to our knowledge, this is the first study assessing maternal and neonatal outcomes in a population sampled both in the first trimester and in the perinatal period [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%